Population Dynamics of the Crocodile Shark, Pseudocarcharias kamoharai, in the Tropical Equatorial Pacific Ocean, Ecuador - Marcos Douglas Calle-Morán; Eugenio Alberto Aragón-Noriega; Ana Rosa Hernández-Téllez; Emigdio Marín-Enríquez; Javier Tovar-Ávila; Juan Francisco Arzola-González; Jorge Payán-Alejo (Fishes)
The objectives of this study were to determine the rates of natural mortality (M), fishing mortality (F), total mortality (Z), the exploitation rates (E), as well as the biological reference points (BRPs) and the annual removal rates (R) of the crocodile shark, Pseudocarcharias kamoharai, in the Ecuadorian Pacific. Thirty similar and different models were applied to determine all these rates. These equations were obtained from studies on teleost and chondrichthyan fish. The biological parameters, including age, growth, longevity, and reproduction, were obtained from the specialized literature based on the biology of P. kamoharai in Ecuadorian waters. These biological parameters were used in all the models considered here. The M estimations were 0.14 to 0.28 based on six models for chondrichthyans and osteichthyes. These values were similar to the six algorithms designed for cartilaginous fish, ranging from 0.16 to 0.35; for this reason, these mortality rates were considered low. The Z values ranged from 0.08 to 0.51; however, they were not considered given that the three estimations were less than M, and only the Z = 0.51 was considered. Given that Z = 0.51 and M = 0.24, an F = 0.27 was obtained by subtraction, indicating a low mortality by fishing. E had values between 0.21 and 0.53, which indicated overexploitation that exceeded the Eopt = 0.50 value. The obtained BRPs were Fopt = 0.10 and 0.12 and Flim = 0.16, which showed that the optimal fishing levels (best possible capture) to achieve long-term sustainable exploitation of the stock encompass 10 to 16% of the fishing effort applied for this species. However, the F surpassed this prudential range. The annual removal percentage (R = 21%) demonstrated that 21% of the population was being removed. Based on the biology and ecology of this species, all models applied in this study showed that P. kamoharai had low natural and fishing mortality rates and moderate total mortality; its exploitation rate exceeded the fishing limits. These values and their life history traits indicated that this shark species cannot tolerate any fishing level without threatening its populations.